Targeted DamID in C. elegans reveals a direct role for LIN-22 and NHR-25 in antagonising the epidermal stem cell fate - Katsanos,D; Barkoulas,M (Science Advances, 2022)
Transcription factors are key players in gene networks controlling cell fate specification during development. In multicellular organisms, they often display complex patterns of expression and binding to their targets, hence tissue-specificity is required in the characterisation of transcription factor-target interactions. We introduce here Targeted DamID (TaDa) as a method for tissue-specific transcription factor target identification in intact C. elegans animals. We employ TaDa to recover targets in the epidermis for two key transcription factors, the HES1 homologue LIN-22 and the NR5A1/2 nuclear hormone receptor NHR-25. We demonstrate a direct link between LIN-22 and the Wnt signalling pathway through repression of the Frizzled receptor lin-17. We also find a direct role for NHR-25 in promoting cell differentiation via repressing the expression of stem cell-promoting GATA factors. Our results expand our understanding of the epidermal gene network and highlight the potential of TaDa to dissect the architecture of tissue-specific gene regulatory networks.